Encapsulation of probiotic strains in plain or cysteine-supplemented alginate improves viability at storage below freezing temperatures - Sousa, Sérgio (2019)
Four probiotic bacteria (Lactobacillus paracasei L26, L. casei-01, L. acidophilus Ki, and Biﬁdobacterium animalis BB-12 R ) were encapsulated in plain alginate or alginate supplemented with L-cysteine·HCl, and resulting microcapsules were stored at differenttemperatures,namely21,4,−20,or−80◦Cforaperiodofupto6months. The results showed that the encapsulation in calcium alginate microcapsules was only effective in promoting protection at freezing temperatures, independently of the sensitivity of the strain. Storage of calcium alginate microcapsules at−80◦C indicatedaprotectiveeffectuponviabilityofallfourprobioticstrainsandthepresence of L-cysteine·HCl in the alginate matrix improved protection upon cell viability of B. animalis BB-12 R . An increase in storage temperature of encapsulated bacteria caused an increase in rate of loss in their viability that was strain dependent. This study suggests that microencapsulation of probiotic cells in calcium alginate can be suitableforsustainingtheviabilityofprobioticsinfoodproductsthatrequirestorage below freezing temperatures, even in the absence of cryoprotectors, contributing to an increased shelf life.